2017
DOI: 10.2174/1874847301705010009
|View full text |Cite
|
Sign up to set email alerts
|

Justification of Traditional Uses of Asparagus Racemosus (Shatavari) - A Miracle Herb

Abstract: Objective: The ethanolic plant extracts of Asparagus racemosus and their partitionates were assessed for thrombolytic, membrane stabilizing, antimicrobial and antioxidant activity in vitro. Methods: The collected plant was dried and grinded. The coarse powder was shocked in 2000 mL of 90% methanol for several days then filtrated. At 40°C the volume of crude ethanolic extract (CEE) was reduced by a vacuum rotary evapor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…racemosus is an extensively used herb in Ayurvedic medicine system. This spinous under shrub commonly grows at low altitudes of tropical and subtropical countries [49]. In in vivo experimental models, this species has shown significant reduction of rat paw edema induced by carrageenan and serotonin [50,51].…”
Section: Asparagus Racemosus Willdmentioning
confidence: 99%
See 1 more Smart Citation
“…racemosus is an extensively used herb in Ayurvedic medicine system. This spinous under shrub commonly grows at low altitudes of tropical and subtropical countries [49]. In in vivo experimental models, this species has shown significant reduction of rat paw edema induced by carrageenan and serotonin [50,51].…”
Section: Asparagus Racemosus Willdmentioning
confidence: 99%
“…In in vivo experimental models, this species has shown significant reduction of rat paw edema induced by carrageenan and serotonin [50,51]. Whereas in vitro assays demonstrated that this plant has promising RBC membrane stabilization activity [49,52,53]. A. racemosus extract demonstrated anti-inflammatory activity by reducing pathology of inflammatory bowel disease (IBD) in oxazolone induced zebra fish IBD (inflammatory bowel disease) model [54].…”
Section: Asparagus Racemosus Willdmentioning
confidence: 99%
“…The clear supernatant was decanted, and remaining RBC cells were undertaken for membrane stabilizing activity. Finally, cellular components (0.5 ml erythrocyte suspension, 5 ml hypotonic solution, and 50 mM NaCl in 10 mM sodium phosphate buffered saline) were well mixed for in vitro membrane stabilizing assay [29].…”
Section: Sample Preparation For Membrane Stabilization Assaymentioning
confidence: 99%
“…In Ayurveda, this unique herb is called as "Queen of herbs" because it promotes love and devotion (Pandey et al, 2021) [3] . Asparagus racemosus is one unique drugs in Ayurveda and effective in treating madhur vipakam, seet -veeryam, somrogam, chronic fever and internal heat (Karim S. et al, 2017) [4] . Charak Samhita and Ashtang Hridyam, the two main texts on ayurveda medicines uses Asparagus racemosus for the formula to treat women's health disorder.…”
Section: Introductionmentioning
confidence: 99%